Femtosecond-laser sharp shaping of millimeter-scale geometries with vertical sidewalls. (18th November 2021) - Zhu, Qiuchi; Fan, Peixun; Li, Nan; Carlson, Timothy; Cui, Bai; Silvain, Jean-François; Hudgins, Jerry L; Lu, Yong Feng
Abstract: As femtosecond (fs) laser machining advances from micro/nanoscale to macroscale, approaches capable of machining macroscale geometries that sustain micro/nanoscale precisions are in great demand. In this research, an fs laser sharp shaping approach was developed to address two key challenges in macroscale machining (i.e. defects on edges and tapered sidewalls). The evolution of edge sharpness (edge transition width) and sidewall tapers were systematically investigated through which the dilemma of simultaneously achieving sharp edges and vertical sidewalls were addressed. Through decreasing the angle of incidence (AOI) from 0° to −5°, the edge transition width could be reduced to below 10 µ m but at the cost of increased sidewall tapers. Furthermore, by analyzing lateral and vertical ablation behaviors, a parameter-compensation strategy was developed by gradually decreasing the scanning diameters along depth and using optimal laser powers to produce non-tapered sidewalls. The fs laser ablation behaviors were precisely controlled and coordinated to optimize the parameter compensations in general manufacturing applications. The AOI control together with the parameter compensation provides a versatile solution to simultaneously achieve vertical sidewalls as well as sharp edges of entrances and exits for geometries of different shapes and dimensions. Both mm-scale diameters and depths were realized with dimensional precisions below 10 µ m and surface roughness below 1 µ m. This research establishes a novel strategy to finely control the fs laser machining process, enabling the fs laser applications in macroscale machining with micro/nanoscale precisions. Highlights: A fs laser sharp shaping approach is presented for achieving micro/nanoscale precisions in macroscale machining. Sharp edges and vertical sidewalls are simultaneously achieved by AOI control and parameter compensations. Through adjusting AOI, the edge transition width is reduced to below 10 µ m but at a cost of increased sidewall tapers. Through parameter compensations, non-tapered sidewalls are produced for various macroscale geometries with <10 µ m precisions and <1 µ m surface roughness. Sidewall tapers are tuned from positive to negative by controlling fs laser ablation via parameter compensation.